Pengadaan Koleksi Muatan Lokal â€œLocal Content â€sebagai Upaya Pelestarian Budaya Daerah di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Putri, Cici Anjelina; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThe writing of this paper aims to describe: (1) local content collection services, (2) constraints in procuring local content collections; and (3) efforts in procuring local content collections in the Archives Service and West Sumatra Province Library. The method of writing this paper is to use a qualitative descriptive method which is done by observation, interviews and data collection directly to the source, the Office of Archives and the Library of West Sumatra Province. Based on the results of interviews and observations conducted at the Archives Service and West Sumatra Province Library are as follows: First, the service collection of "local content" content at the Archives Service and West Sumatra Province Library through the procurement of local content collection, local content collection service system and the use of collections local content by users in the Archives Service and Library of West Sumatra Province. Second, the obstacles faced are: (1) limited number of local content collections, (2) limited access to local content collections, (3) lack of government and other related parties' attention to cultural functions, (4) lack of human resources as skilled librarians. Third, the efforts that have been made by the Office of Archives and Library of West Sumatra Province, namely conducting education, outreach, law enforcement and infrastructure facilities for local content collection works in an effort to preserve regional culture.Keyword: local content collection; cultural preservation; public library